تحسين تقنيات انتاج غراس الخرنوب Ceratonia siliqua L. في المشتل وتأثيرها على نسبة البقاء في الأرض الدائمة - صالح مأمون; علاء الدين حسن إبراهيم; علي وائل (Latakia University Journal -Biological Sciences Series, 2013)
هدف هذه الدراسة تحديد حجم الأوعية وشكلها الأفضل لإنتاج غراس أكثر جودة، وتحديد أي المعالجات (تحريك الغراس الى مراقد اخرى أو نقلها إلى أوعية أكبر حجماً أو تقليم المجموعين الخضري والجذري لغراس الخرنوب في المشتل) أفضل على النمو والاستقرار في الأرض الدائمة. بينت الدراسة أن غراس الشاهدD1 النامية في أوعية(أكياس) بلاستيكية تقليدية سعة 1 ليتر، أعطت نسبة بقاء منخفضة لا تتجاوز الـ 20%، يعود ذلك إلى عدة نواحٍ أهمها تشوه المجموع الجذري والتفافه في قعر الوعاء أو خروجه من إحدى فتحاته الى تربة المشتل، أما غراس D8 فقد حسنت الأوعية سعة 2 ليتر الصفات المورفولوجية للمجموعين الجذري والخضري وقللت من تشوه الجذور، مما أدى الى نسبة بقاء مرتفعة بلغت أكثر من 82%، أما غراس D9 فقد حسنت الأوعية العميقة واجراء التقليم الهوائي من بنية وانتشار المجموع الجذري وحدت من تشوهات التفاف الجذور، مما أدى إلى نسبة بقاء مرتفعة بلغت أكثر من %95. أما تحريك الغراس إلى مراقد اخرى في المشتل حسن من نسبة بقاء الغراس حية في الأرض الدائمة ، حيث بلغت في D2 أكثر من 95%، وفي D3 أكثر من 67%. كما بينت الدراسة أن قص القمة النامية للمجموع الخضري وترك الغراس في مرقدها حتى موعد زراعتها في الأرض الدائمة في D4 لم تعط تاثيراً معنوياً بالمقارنة مع غراس D5 التي تم قص القمة النامية لمجموعها الخضري ونقلت إلى أكياس سعة 12 ليتر مع تقليم المجموع الجذري، وبلغت نسبة البقاء أكثر من 72% في D4 ، وأكثر من 62% في D5، أما فيما يخص نسبة بقاء الغراس تحت تأثير عمليات النقل إلى أكياس أكبر حجماً، فقد تفوقت D7(77.5%) التي نقلت غراسها إلى أكياس سعة 3 ليتر بفروقات معنوية واضحة على D5 ،D6 التي نقلت غراسها إلى أكياس سعة 12 ليتر، والتي بلغت نسبة البقاء فيهما 62.5%. The aim of this study was to determine the best size and shape of containers to produce higher quality seedlings, and determine which treatments (moving the seedlings to other beds, or transfer to bigger containers, or pruning the shoot and root system of Ceratonia siliqua seedlings in the nursery) are the best for growth and stabilization in out planting. The study showed that the control seedlings D1 which were growing in traditional plastic containers (1 liter) gave low survival rate which did not exceed 20%, and this was due to numerous reasons mainly roots deformation. Seedlings D8, the containers(2 liters) improved the morphological characteristics of root and shoot system and reduced the roots deformation, which led to higher survival rate reached more than 82%. While the deep containers and the air pruning improved the structure and spread the root system of seedlings D9 and limited the roots deformation, which led to higher survival ratio reached more than 95%. Moving the seedlings to other beds in the nursery improved the survival rate in out planting, which amounted ,in D2, to more than 95% and in D3 over than 67%. Also, the study confirmed that cutting the developing top of shoot system and leaving the seedlings in the beds until their planting date D4 did not give a significant effect compared to D5 in which the developing top of their shoot system was cut and was transferred to bags of (12 liters) with pruning the root system, and the survival rate was more than 72% in D4, and over 62% in D5. Regarding to survival rate under the influence of transport operations to larger bags, the D7 which was transferred to bags of 3 liters capacity surpassed in significant differences and was 77.5% compared to D5 and D6 which was transferred to 12 liters bags, where the survival rate in which was 62.5%.